Development of a shear forming envelope for carbon fibre non-crimp fabrics. Issue 2 (June 2022) - Lux, Benedikt; Fial, Julian; Schmidt, Olivia; Carosella, Stefan; Middendorf, Peter; Fox, Bronwyn
Our research aims to develop a shear forming envelope for the preforming of textiles, a critical step in the manufacture of fibre-reinforced composite materials. This paper demonstrates the progress towards this aim by conducting picture frame tests to empirically determine the locking angle of non-crimp fabrics with different fibre orientations. While conventional shear tests typically utilise woven textile samples with orthogonal fibre directions of 0°/90°, the investigation of non-crimp fabrics, especially with non-standard fibre orientations, is less common. As a result, there is little knowledge about the shear deformation behaviour of these fabric types, despite their relevance to the aerospace industry. In this study, the shear locking angles of various carbon fibre non-crimp fabrics are investigated, gradually reducing the relative fibre angles of the textile materials from ±45° to ±22.5°. Previously, it was observed that unidirectional 0° reinforcement layers induce draping defects when forming multiaxial non-crimp fabric stacks into curved aerospace stiffeners. Their substitution by reinforcements with smaller cross-ply angles such as ±30° resulted in better formability and reduced defects. It is however unclear, how the shear locking angle decreases with more acute cross-ply angles. Here, we report for the first time a correlation between the fibre orientation of the non-crimp fabric and its shear locking angle. The resulting shear forming envelope provides composite design and manufacturing guidance for an enhanced utilisation of the advantageous but anisotropic properties of carbon fibre textiles.